Αναδυόμενες ταυτότητες και εθνικότητα σ’ ένα φλιτζάνι κυπριακού καφέ - Zantides, Evripides (My University, 2016)
National identity is not only an outcome of a common origin, history, tradition or common ideals and a shared cultural background of a nation as usually defined, but as Edensor (2002) suggests, national identity is also an arrangement of various other aspects whose origins are structured in the practices of the quotidian and in popular culture. Anderson (1997) builds upon cultural factors and defines the nation as an imagined political community, which has been strongly influenced and revised by, among other things, the advent of the printing press in the mid-15th century. The evolution of printing methods generates new means of communication that contribute to the shaping of a collective national consciousness, and impact both the notion and the dissemination of the idea of a nation. This paper is based on Anderson’s theory, and aims through a Visual Analysis of printed advertisements of Laiko Kafekopteio of Cyprus-The People’s Coffee of Cyprus, to explore and draw conclusions regarding representations relating to Cypriot national identity.
Changing Worlds & Signs of the Times: Selected Proceedings from the 10th International Conference of the Hellenic Semiotics Society
Keywords: National identity; Print advertisement; Semiotic analysis